Medium-dependent Alteration of Lysine Transfer Ribonucleic Acid in Sporulating Bacillus subtilis Cells - Lazzarini, Robert A. (1967)
The presence of the altered lysine transfer ribonucleic acid (tRNA) in Bacillus subtilis spores is strongly dependent on the medium on which the cells were sporulated. Cells sporulated on synthetic media or dilute complex media contain little or none of the new component, whereas those sporulated on concentrated complex media accumulate the altered tRNA. The accumulation begins during the fifth or sixth stage of sporulation, the formation of the tunic, and the appearance of refractility, respectively. Mutants blocked early in sporulation differ in their ability to accumulate the altered tRNA when cultured on the same complex medium. Of the four mutants examined, one failed to accumulate any of the RNA, whereas a second contained the full complement characteristic of spores. The third and fourth mutant contained small amounts of the material. It is tentatively concluded that the accumulation of the altered lysine tRNA is not obligate to sporulation but is an epiphenomenon of the process.